1998
DOI: 10.1007/bf03026378
|View full text |Cite
|
Sign up to set email alerts
|

Parametric studies of the mechanical behaviour of porous titanium

Abstract: This paper investigates the prediction of some common mechanical properties of sintered pure titanium. Tensile strength was determined using the radial crush strength method and the fracture toughness tests were performed using disk-shaped compact tension specimens. Empirical models that predict the mechanical behaviour of sintered titanium are reported in this paper and compared with other models like those of HashinStrikman, Fleck and Smith, Griffiths et al. and Nielson.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The compositions of the binary powder particle mixture and pore diameter appear to have less effect on the tensile properties of porous Ti compacts than the overall level of porosity. A number of research studies have indicated that porosity is the dominant influence on the mechanical properties of sintered Ti [1,21,[35][36][37]. Oh et al reported results for the compressive and three point bending strengths of porous Ti compacts made by a press and sintering route using spherical powder particles with a range of particle sizes [1].…”
Section: Tensile Propertiesmentioning
confidence: 97%
“…The compositions of the binary powder particle mixture and pore diameter appear to have less effect on the tensile properties of porous Ti compacts than the overall level of porosity. A number of research studies have indicated that porosity is the dominant influence on the mechanical properties of sintered Ti [1,21,[35][36][37]. Oh et al reported results for the compressive and three point bending strengths of porous Ti compacts made by a press and sintering route using spherical powder particles with a range of particle sizes [1].…”
Section: Tensile Propertiesmentioning
confidence: 97%